Mixed magnetoconvection in a lid-driven cavity with a sinusoidal wavy wall and a central heat conducting body - Nasrin, Rehena (Journal of Naval Architecture and Marine Engineering, 2011)
A numerical study has been performed to explore the mixed magnetoconvective flow and heat transfer characteristics of fluid contained in a lid-driven cavity having a sinusoidal wavy vertical surface. A heat conducting square body is located at the centre of cavity. The cavity horizontal walls are perfectly insulated while the corrugated right vertical surface is maintained at a uniform temperature higher than the left lid. The flow is assumed to be two-dimensional and Joule heating effect is considered. Calculations are carried out through solving governing equations for different parameters by using Galarkins weighted residual finite element method. The flow pattern and the heat transfer characteristics inside the cavity are presented in the form of streamlines, isotherms, average temperature of the fluid and temperature of solid body centre for various values of Prandtl number Pr, Richardson number Ri and magnetic parameter Ha. The heat transfer rate is detected maximum for the highest Pr and absence of magnetic field. DOI: http://dx.doi.org/10.3329/jname.v8i1.6793